En busca del concepto de cine nacional Español - Lénárt, András (Acta Hispanica, 2012)
The aim of this paper is to analyse the notion of Spanish "national dnema" from achronological perspective and to search for a possible answer to the question if there is a reasonto reflect on this expression in case of Spain. Since the arrival of the dnematograph at thepeninsula, the theoretical approaches ofpoliticans, ideologists and filmmakers to this problemhave produced a wide range of movies which have given a subjective perception about someauthentic or false characteristics of the Spaniards. The consecutive administrations had differentand often inconsistent attitudes towards their own national dnematographic representation:while the Second Republic practically neglected the shaping of this audiovisual self-definition,the Franco regime laid by far the largest emphasis on creating the ultimate patriotic nationaldnema. Nowadays it is even more complicated, if not impossible, to identify the nature of thecontemporary Spanish national film industry. We will touch upon genres, movies, stereotypes,personal impressions and ideological argumentations in order to examine what national dnemameans in the Spanish context.